The Selection process : choosing the right man for the job - Mandell, Milton M. (Bombay : D.B. Taraporevala Sons & Co. Private Ltd, 1970)
This Book is addressed to the personnel director and his staff members who want a comprehensive discussion of selection methods; to the executive and the supervisor who want to improve their effectiveness in recruiting, interviewing, and reference checking and who would like to learn about the esoteric field of testing; to the psychologist who wants to learn about industrial practices; and to graduate and undergraduate students in business and public administration, personnel management, and industrial psychology. I have obtained much assistance in writing and assembling the materials for this work.
Part One. Overview -- Part Two. Methods -- Part Three. Occupational Group.
Includes bibliographical references and index.
Keywords: PERSONNEL MANAGEMENT